PROTECTIVE EFFECT OF DEXMEDETOMIDINE - O. N. Ulitkinа; O. A. Grebenchikov; Yu. V. Skripkin; F. F. Bershаdskiy (Вестник анестезиологии и реаниматологии, 2018)
Currently, the issue of organ protection is being actively studied. According to results of a big number of studies conducted all over the world, dexmedetomidine, the agonist of α2-adrenoreceptors, possesses certain protective properties. Further multi-center randomized studies are needed in order to prove that this drug can be used to reduce the number of peri-operative complications and the risk of organ dysfunction, and to improve outcomes of surgical treatment in patients with cardiac and non-cardiac operations.